Charakterisierung des Einflusses neigungsinduzierter Strömungsformen mit dem Ansatz der hydrodynamsichen Analogie - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Modellierung des Randspalts in Strukturpackungskolonnen mit dem Ansatz der hydrodynamischen Analogien - Ehlert, Thomas; Lutters, Nicole; Kenig, Eugeny Y.

Thermal conductivity of solid paraffins and several n-docosane compounds with graphite - Paul, Andreas; Baumhögger, Elmar; Dewerth, Mats-Ole; Hami Dindar, Iman; Sonnenrein, Gerrit; Vrabec, Jadran (Journal of Thermal Analysis and Calorimetry)
The technical importance of paraffins as phase change materials (PCM) in heat storage systems increases. Knowledge on the thermal conductivity of paraffins is necessary for the design and optimization of heat storage systems. However, for most paraffins solely the thermal conductivity of the liquid state has been sufficiently investigated. For the solid state, precise thermal conductivity data are only known for a few paraffins, while only generalized values are available for the remainder, some of which contradict each other. In this study, a measurement setup based on the modified guarded hot plate method is developed. It is used to investigate the thermal conductivity of several paraffines in the solid state, including pure n-docosane and its compounds with different types and concentrations of graphite. For n-docosane in the solid state, the thermal conductivity is determined to be 0.49 W/(m K). A particle size of 200 μm with a spherical shape turns out to be optimal to increase the thermal conductivity. This allows the thermal conductivity of a compound with 10% graphite to increase by a factor of three compared to the pure paraffin. Furthermore, significant differences to thermal conductivity data from the literature are found.
Keywords: Physical and Theoretical Chemistry; Condensed Matter Physics

Wässrige Glucosaminlösung als neues Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppen Fluidverfahrenstechnik und Adsoprtion)

Simulation des „viscous fingering“ Effektes in Klebverbindungen - Salten, Alexander Heinrich Johannes; Al Trjman, Mohamad; Meschut, Gerson; Kenig, Eugeny Y.

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

Numerische Untersuchung von Oberflächenstrukturierung zur Erhöhung der Effizienz von Kissenplatten-Wärmeübertragern - Afsahnoudeh, Reza; Holzmüller, Maik; Bader, Fabian; Homberg, Werner; Kenig, Eugeny Y.

Thermo-hydraulic Performance of Pillow-Plate Heat Exchangers with Secondary Structuring: A Numerical Analysis - Afsahnoudeh, Reza; Wortmeier, Andreas; Holzmüller, Maik; XGong, Yi; Homberg, Werner; Kenig, Eugeny Y. (Energies)

CFD-Untersuchungen der Fluiddynamik und des Wärmetransports an rauen Oberflächen - Hollenhorst, Viola; Kenig, Eugeny Y.

Modellierung der Reaktivabsorption in regellosen Schüttungen und modellbasierte Optimierung von Füllkörpern mit dem Ansatz der hydrodynamischen Analogien - Salten, Alexander Heinrich Johannes
Füllkörper spielen in industriellen Trennprozessen eine wichtige Rolle bspw. bei der Reinigung industrieller Abgase durch Absorption. Die Trennleistung von Füllkörperkolonnen wird üblicherweise mittels vereinfachter Stufenmodelle ermittelt, deren Modellparameter experimentell bestimmt werden müssen. Dies stellt eine große Schwäche von Stufenmodellen dar, da diese Parameterim Allgemeinen nicht auf verschiedene Stoffsysteme und Füllkörpertypen übertragbar sind.In dieser Arbeit wird ein Modell, basierend auf dem hydrodynamischen Analogieansatz, zur Beschreibung von Absorptionsvorgängen in Füllkörperkolonnen vorgestellt. Dabei ist die Geometrie der festen Phase direkt abhängig von der Füllkörpergeometrie und der Stochastik der Schüttung. Die tatsächlichen Strömungsverhältnisse in Füllkörperkolonnen werden erfasst und durch eine Kombination vereinfachter charakteristischer Strömungsformen reproduziert. Dies erlaubt die Verwendung rigoroser Transportgleichung. Dadurch enthält das Modell weniger experimentell zu ermittelnde Parameter und ist damit unabhängiger von Experimenten als vereinfachte Stufenmodelle. Das Modell wurde gegen experimentelle Daten zur CO2-Absorption in wässrige Natronlauge validiert. Mit dem entwickelten Modell wurde anschließend eine Parameterstudie durchgeführt, die der Unterstützung der Entwicklung neuer Füllkörpergeometrien dient. Dazu wurde eine Simulationsstudie durchgeführt, die den Einfluss der Füllkörpergeometrie auf die Trennleistung untersucht.

Demand Side Management Implementation in Downstream Digestate Treatment of a Biomethane Biorefinery - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Chemical Engineering Transactions)

Experimentelle Untersuchung und Modellvalidierung zur Gravidestillation - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Jahrestreffen der ProcessNet Fachgruppen Fluidverfahrenstechnik und Hochdruckverfahrenstechnik)

Heat regeneration model for external heat engines operating with dense working fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Annual Meeting on Reaction Engineering and ProcessNet Subject Division Heat and Mass Transfer)

Innovative Leichtbau- und Kühlungskonzepte für elektrische Maschinen durch additive Fertigung (ILuKadd3D) - Haase, Michael; Tasche, Frederik; Bieber, Maximilian; Zibart, Alexander

Entwicklung eines innovativen Trennapparates zur Stickstoffrückgewinnung aus landwirtschaftlichen Abfällen - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

Untersuchung von Gefahrensituationen bei industriellen Absorption/Desorption-Prozessen mittels dynamischer Simulation - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Development of an innovative separation unit for nitrogen recovery from agricultural waste - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny
Keywords: CFD; simulation; agricultural waste; multiphase

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (1st Conference on Energy, Environment and Digital Transition E2DT)

Effect of diffusivity and chemical reactions on the determination of mass transfer coefficients in columns with structured packing - Mapura, Luz Alejandra; Kenig, Eugeny Y. (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Experimental study on the condensation of pure substances in outer pillow-plate channels - Buckmann, Felix; Kenig, Eugeny (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Liquid flow morphology investigation in structured packings for offshore applications using a novel flow imaging sensor - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.

Untersuchung von kleinskaligen Flüssigkeitselementen auf mikrostrukturierten Packungsoberflächen - Dechert, Christopher; Kenig, Eugeny

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (Chemical Engineering Transactions)

CFD-Based Investigation of the Packing Microstructure Influence on Droplet Behavior and Film Flow - Dechert, Christopher; Kenig, Eugeny (Proceedings of the 12th international conference Distillation & Absorption 2022)

On Heat Regeneration Limitations in Heat Engines With Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Heat Powered Cycles Conference 2022)

Modellierung des Stofftransportes in einer geneigten Kolonne mit dem Ansatz der hydrodynamischen Analogien - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Dynamic modeling of absorption/desorption closed-loop including periphery - Bothe, Mike; Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y. (Computers and Chemical Engineering)

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas Markus; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)

Droplet formation –a numerical investigation of liquid-liquid systems with consideration of Marangoni convection - Wecker, Christian; Schulz, Andreas Markus; Heine, Jens; Bart, Hans Jörg; Kenig, Eugeny Y. (International Journal of Heat and Mass Transfer)

Experimentelle Untersuchung der Tropfenkondensation am chemisch modifizierten Edelstahl‐Drallrohr - Dai, Daokun; Kenig, Eugeny Y.; Numrich, Reiner (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

A front-tracking method for two-phase flow simulation with no spurious currents - Inguva, Venkatesh; Kenig, Eugeny Y.; Perot, J. Blair (Journal of Computational Physics)

Determination of the burst pressure of pillow plates using finite element methods - Zibart, Alexander; Spang, Bernhard; Kenig, Eugeny Y. (Computer Aided Chemical Engineering)

Flow in Pillow-Plate Channels for High-Speed Turbomachinery Heat Exchangers - Sundermeier, Stephan; Passmann, Maximilian; aus der Wiesche, Stefan; Kenig, Eugeny Y. (International Journal of Turbomachinery, Propulsion and Power)
In numerous turbomachinery applications, e.g., in aero-engines with regenerators for improving specific fuel consumption (SFC), heat exchangers with low-pressure loss are required. Pil low-plate heat exchangers (PPHE) are a novel exchanger type and promising candidates for high-speed flow applications due to their smooth profiles avoiding blunt obstacles in the flow path. This work deals with the overall system behavior and gas dynamics of pillow-plate channels. A pillow-plate channel was placed in the test section of a blow-down wind tunnel working with dry air, and compressible flow phenomena were investigated utilizing conventional and focusing schlieren optics; furthermore, static and total pressure measurements were performed. The experiments supported the assumption that the system behavior can be described through a Fanno–Rayleigh flow model. Since only wavy walls with smooth profiles were involved, linearized gas dynamics was able to cover important flow features within the channel. The effects of the wavy wall structures on pressure drop and Mach number distribution within the flow path were investigated, and a good qualitative agreement with theoretical and numerical predictions was found. The present analysis demonstrates that pressure losses in pillow-plate heat exchangers are rather low, although their strong turbulent mixing enables high convective heat transfer coefficients.
Keywords: Mechanical Engineering; Energy Engineering and Power Technology; Aerospace Engineering

State-of-the-Art Modeling of Separation Columns: A Review - Kenig, Eugeny Y. (Chemical Engineering Transactions)

Wässrige Aminozuckerlösungen als neue Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Baumhögger, Elmar; Lutters, Nicole; Kenig, Eugeny (Jahrestreffen der ProcessNet Fachgruppen Fluidverfahrenstechnik und Hochdruckverfahrenstechnik)

Flow Morphology of TEG Desiccant in a Structured Packing Air Dehumidifier Exposed to Floating Conditions - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.; Hampel, Uwe (Proceedings of the 12th international conference Distillation & Absorption 2022)

On methods to reduce spurious currents within VOF solver frameworks. Part 1: a review of the static bubble/droplet - Inguva, Venkatesh; Schulz, Andreas; Kenig, Eugeny (Chemical Product and Process Modeling)
Abstract In two-phase flows in which the Capillary number is low, errors in the computation of the surface tension force at the interface cause Front-Capturing methods such as Volume of Fluid (VOF) and Level-Set (LS) to develop interfacial spurious currents. To better solve low Capillary number flows, special treatment is required to reduce such spurious currents. Smoothing the phase indicator field to more accurately compute the curvature or adding interfacial artificial viscosity are techniques that can treat this problem. This study explores OpenFOAM, Fluent and StarCCM+ VOF solvers for the classical case of a static bubble/droplet immersed in a continuous aqueous phase, with the focus on the ability of these solvers to adequately reduce spurious currents. The results are expected to be helpful for practicing chemical engineers who use multiphase CFD solvers in their work.

Modelling and simulation of zero-gravity distillation units with metal foams - Wende, Marc; Staggenborg, Christoph; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Model Based and Experimental Analysis of the Dynamic Reactive Absorption Loop Behavior - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Proceedings of the 12th international conference Distillation & Absorption 2022)

Modeling Concepts for Reactive Separations - Kenig, Eugeny Y. (Process Intensification by Reactive and Membrane-assisted Separations)

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, René; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, Sören Antonius; Kenig, Eugeny (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Heat transfer enhancement with internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.

Numerical and Experimental Investigation of Zero-Gravity Distillation Units - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Chemical Engineering Transactions)

Examination of hazardous situations in industrial closed-loop processes using dynamic simulations - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny (Chemical Engineering Transactions)

Numerical and Experimental Investigation of Zero-Gravity Distillation Units - Wende, Marc; Fischer, Florian; Kenig, Eugeny (24th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (PRES‘21))

Konzeption und Inbetriebnahme eines Versuchsstandes zur Gravidestillation - Wende, Marc; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppen Fluidverfahrenstechnik und Wärme- und Stoffübertragung)

Modellierung eines Latentwärmespeichersystems in Form einer ungeordneten Schüttung makro-verkapselter PCM-Elemente - Grabo, Matti; Kenig, Eugeny

Stofftransportmessung und -visualisierung am ruhenden und bewegten Einzeltropfen - Heine, Jens; Wecker, Christian; Kenig, Eugeny; Bart, Hans-Jörg

Numerische Untersuchung der Marangonikonvektion in Flüssig-Flüssig-Systemen: Von der Tropfenbildung bis zur Tropfeninteraktion - Wecker, Christian; Schulz, Andreas; Heine, Jens; Bart, Hans-Jörg; Kenig, Eugeny